2010
DOI: 10.4103/0971-3026.73528
|View full text |Cite
|
Sign up to set email alerts
|

MRI findings in Hirayama disease

Abstract: The objective of the study was to study the magnetic resonance imaging (MRI) features of Hirayama disease on a 3 Tesla MRI scanner. Nine patients with clinically suspected Hirayama disease were evaluated with neutral position, flexion, contrast-enhanced MRI and fast imaging employing steady-state acquisition (FIESTA) sequences. The spectrum of MRI features was evaluated and correlated with the clinical and electromyography findings. MRI findings of localized lower cervical cord atrophy (C5-C7), abnormal curvat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 12 publications
6
55
0
2
Order By: Relevance
“…Hassan et al in 2012 have reported eleven cases of HD from various regions of India, while Sonwalkar et al in 2008 reported eight cases from South India and Raval et al in 2010 reported nine cases from North India [5, 18, 24]. All patients in these series were males.…”
Section: Clinical Featuresmentioning
confidence: 95%
See 3 more Smart Citations
“…Hassan et al in 2012 have reported eleven cases of HD from various regions of India, while Sonwalkar et al in 2008 reported eight cases from South India and Raval et al in 2010 reported nine cases from North India [5, 18, 24]. All patients in these series were males.…”
Section: Clinical Featuresmentioning
confidence: 95%
“…Sonwalkar et al reported a mean age of 18.5 years (11–24 years) [18], while Raval et al reported a mean age of 18 years (15–23 years) [24]. Hassan et al reported all patients younger than 25 years (median age 23 years; 19–50 years) except one patient who was 50 years old with disease duration of 2 years.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Pathological studies have demonstrated focal degeneration restricted to anterior horn cells in MMA 43. It has been postulated that upper extremity MMA may be a myelopathy related to flexion movements of the neck with resultant ischaemic damage to the anterior horn cells of the cervical cord 44. Alternatively MMA may represent a primary localised neurodegenerative disorder of the anterior horn cell.…”
Section: Pathophysiologymentioning
confidence: 99%